5x - 2y = -6 ⇒ 10x - 4y = -12
2x - 1y = 1 ⇒ <u>10x - 5y = 5</u>
y = -17
5x - 2(-17) = -6
5x + 34 = -6
<u> - 34 - 34</u>
<u>5x</u> = <u>-40</u>
5 5
x = -8
(x, y) = (-8, -17)
2x + 3y = 432 ⇒ 10x + 15y = 2160
5x + 2y = 16 ⇒ <u>10x + 4y = 32</u>
<u>11y</u> = <u>2128</u>
11 11
y = 193.4545455
2x + 3(193.4545455) = 432
2x + 580.3636364 = 432
<u> - 580.3636364 - 580.3636364</u>
<u>2x</u> = <u>-148.3636364</u>
2 2
x = -74.1818182
(x, y) = (-74.1818184, 193.4545455)
Answer:
I'm not sure but I think is 31.4
Step-by-step explanation:
multiply 15.70 twice
Answer:108
Step-by-step explanation:
Answer:
0.23
Step-by-step explanation: